2019
DOI: 10.1186/s12893-019-0493-9
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review comparing two common surgical approaches to the hip for hemiarthroplasty

Abstract: Background Hemiarthroplasty for hip fracture is a common surgical procedure. A number of distinct approaches are used to access the hip joint. The most commonly used are the direct lateral approach (DLA), and the posterior approach (PA). Internationally there is little consensus on which of these approaches to use. Current guidance is based on a limited selection of evidence and choice of approach is frequently based on surgeon preference. Historically, recommendations have been made based on disl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
1
21
1
1
Order By: Relevance
“…Acetabular anteversion angle (AAA), posterior acetabular sector angle (PASA), posterior wall angle (PWA), and acetabular roofing (%) were evaluated from CT scans. Methodology described by Fullam et al [15] was used for radiological evaluation. In short, an inter-capital centre line (ICL) was drawn on true axial images through both femoral heads at the point of maximum diameter in all 3 planes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetabular anteversion angle (AAA), posterior acetabular sector angle (PASA), posterior wall angle (PWA), and acetabular roofing (%) were evaluated from CT scans. Methodology described by Fullam et al [15] was used for radiological evaluation. In short, an inter-capital centre line (ICL) was drawn on true axial images through both femoral heads at the point of maximum diameter in all 3 planes.…”
Section: Methodsmentioning
confidence: 99%
“…Dislocation after BHA seems to be independent from the surgical approach [15]. A recent study has reported that posterior wall acetabular morphology may influence hip stability [16].…”
Section: Introductionmentioning
confidence: 98%
“…Rogmark and Leonardsson published a review of RCTs and register studies reporting an increased risk of dislocation with PA, and given the seriousness of dislocations they suggest that DLA is preferable (89). A recent review article by Fulham (2019) on DLA versus PA described observational studies (85,(90)(91)(92) recommending the DLA based on higher risk of posterior dislocation, but concluded that the evidence is limited and that the topic needs further investigation (93 probably less used due to its learning curve and surgeons' choice (106).…”
Section: Surgical Approachesmentioning
confidence: 99%
“…Many surgical approaches are used in THA surgery, but there is little evidence indicating which approach has the most advantages [5,6] . On the one hand, the direct anterior approach (DAA) is considered a true minimally invasive approach because it leads to a small amount of muscle damage, as the operation is performed through a small incision and a muscle gap in the hip joint [7,8] .…”
mentioning
confidence: 99%